EXPLORING THE IMPACT OF FREE VOLUNTARY READING IN UPGRADING UNIVERSITY STUDENTS' CREATIVE WRITING AT AL BAHA UNIVERSITY - Osama Yousif Ibrahim Abualzain (University of Kuningan, 2017)
The purpose of this study is to investigate the impact of free voluntary reading in upgrading university students' creative writing at Al-Baha University. It introduces the types of free voluntary reading that can be employed by the students. In order to achieve this, thirty students at Al-Baha University enrolling in the BA program in English department were chosen randomly. The descriptive analytic method then applied in this study. Pre-test and post-test designed for the students and a questionnaire directed to the teachers were used as tools of collecting data. Finally, the results revealed that free voluntary reading plays critical roles in upgrading the students’ creative writing. Also, the teachers highly appreciate the contributions of free voluntary reading materials in pushing forward the students' achievement. Keywords: free voluntary reading, university students, BA program, creative writing